The Similarity of Perceptions on Semester Learning Plan for General Course Environmental Study Based on Disaster Mitigation - Jamhari, Mohammad; Agni, Raya; Zainal, Syech; Sabran, Moh. (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This study aims to analyze the disaster mitigation-based semester learning plan for the general course of living environment studies at Tadulako University. Methodology: This is a descriptive qualitative study employing purposive sampling and survey methods using questionnaires. Data were analyzed through data reduction, data presentation, and conclusion drawing. Thirty respondents participated in the study. Main Findings: Findings reveal that semester learning plan development indicators require seminars and workshops with experts, faculty, students, and alumni. The semester learning plan integrates disaster mitigation-oriented learning outcomes using case methods and team-based projects supported by field practice. semester learning plan implementation aligns with lecturers' improvisation, and periodic reviews are recommended every three years. Novelty/Originality of this study: The study provides a framework for integrating disaster mitigation into the semester learning plan for general course of living environment studies, highlighting practical approaches like case methods and field projects. It advances the integration of disaster education into university-level environmental curricula.